PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MINIMARKET RAYA BOGOR PEKAYON - Stianingrum, Nazah Anggun; Nurhayaty, Ety (LP2M Universitas Bina Bangsa, 2024)
Companies in the retail sector are increasing and growing rapidly. One of the retail companies is the Bogor Pekayon Raya Minimarket, which sells a variety of basic necessities and remains the main choice of consumers. The behavior of consumers who will shop will certainly be influenced by price factors and product quality when making a purchase decision. The purpose of this study is to determine the influence of price and product quality on consumer purchase decisions at the Bogor Pekayon Raya Minimarket. The analysis method in this study uses primary data with the test stages carried out are validity test, reliability test, normality test, heterosexuality test, multicollinearity test, multiple linear regression test, t test, f test, determination coefficient test. The sampling method in this study is by simple random sampling technique, distributing questionnaires to 99 respondents using the Slovin formula. Testing tools using SPSS version 20. The results showed that the price had a positive and significant effect on the purchase decision with the results of the t-test, namely the t>-count value of the table 3.735>1.660 and the significance of 0.000<0.05, while the product quality had a positive and significant effect on the t-test results, which was the t-test value of 8>ttable 8.203>1.660 and the significance of 0.000<0.05, while the result of the f>-test was 131>3.09 and the significance of 0.000<0.05. That there is a simultaneous influence of price and product quality on purchase decisions